Improving primary literacy linking home and school - Feiler, Anthony (TLRP improving practice series, 2007)
"With a focus on improving children's literacy skills, this book provides practical answers to key questions that are directly relevant to all primary teachers and to many parents. It presents new ways of linking learning in home and school through a range of activities that can be used to share knowledge between children, parents and teachers."--Publisher's description.